Seasonality in the condition and variability in somatic relationships of megrim (Lepidorhombus whiffiagonis) in the northeast Atlantic. (5th September 2022) - Landa, J.; Korta, M.; Iriondo, A.; Fontenla, J.; Gancedo, R.; Reparaz, M.; Rodríguez-Fernández, L.; Loureiro, I.; Gómez, A.; Castro, B.; Antolínez, A.; Bruno, I.; et al.
Abstract: Somatic parameters' estimation of megrim ( Lepidorhombus whiffiagonis ), an economically important flatfish species and relevant one in the benthic community, is essential in fisheries biology. It helps us to deepen our understanding of the species life history traits and an adequate stock assessment and fishery management. Le Cren's condition factor (K), weight-length relationships and weight conversion factors were studied in megrim for more than two decades time-series (1998–2019) and wide area with a relevant fishing activity and the species is distributed into two stocks: northern Bay of Biscay-nBB and Celtic Sea-CS stock, and southern Bay of Biscay-sBB and Galician waters-Gw stock. Around 30, 000 specimens, mostly collected from commercial landings by the research institutions IEO and AZTI, were sampled. Total fish length, total weight and commercial gutted weight were obtained, and five-year periods were defined throughout in the time-series. The influence of several factors, as seasonality, temporality, fish sex, maturity, abundance, and environmental conditions on the megrim condition were analyzed for each stock by GLM, being the season the most relevant factor. A clear seasonal pattern found for K, with the lowest values in spring, was found in both populations for the first time based on a multi-year period analysis. The pattern was more prominent in females and less marked in immature, related tothe reproduction process. The lowest condition value was observed in May in nBB-CS and a month earlier in sBB-Gw (both after the spawning period). A progressive increase (favorable feeding conditions) followed to highest values in November–February, showing the relevance of K as indicator of the nutritional/reproductive status of megrim. Temporality (five-year periods) also had a much smaller effect on condition than seasonality. Megrim condition was inversely related to its abundance, and to the NAO index in the nBB-CS stock. Total weight-length, gutted weight-length and total weight-gutted weight relationships were fitted for each megrim stock and their temporal variations were analyzed. The large sample size, size range and time-series available allowed obtaining robust somatic parameters for the total weight-length relationships (a = 0.0049, b = 3.1012; a = 0.0041, b = 3.1682, respectively in nBB-CS stock and sBB-Gw stock), gutted weight-length relationships (a = 0.0046, b = 3.1033; a = 0.0042, b = 3.1510, respectively in nBB-CS and sBB-Gw stock), and weight conversion factors (1.049; 1.056, respectively in nBB-CS and sBB-Gw stock). They were considered the most appropriate to be used in the stock assessment of both stocks. A historical analysis of the temporal variability of the weight-length relationships showed different trends between stocks. Highlights: Somatic relationships for megrim based on two decades of information. Seasonal pattern in megrim condition in two stocks and more prominent in females. Lowest condition in May in northern and a month earlier in the southernmost stock. Robust parameters from a large sample available for stock assessment and management. Historical weight-length relationship variability shows different trend by stock.